Evidence for the Formation of an Enamine Species during Aldol and Michael‐type Addition Reactions Promiscuously Catalyzed by 4‐Oxalocrotonate Tautomerase. Issue 5 (26th February 2015) - Poddar, Harshwardhan; Rahimi, Mehran; Geertsema, Edzard M.; Thunnissen, Andy‐Mark W. H.; Poelarends, Gerrit J.
Abstract The enzyme 4‐oxalocrotonate tautomerase (4‐OT), which has a catalytic N‐terminal proline residue (Pro1), can promiscuously catalyze various carbon–carbon bond‐forming reactions, including aldol condensation of acetaldehyde with benzaldehyde to yield cinnamaldehyde, and Michael‐type addition of acetaldehyde to a wide variety of nitroalkenes to yield valuable γ‐nitroaldehydes. To gain insight into how 4‐OT catalyzes these unnatural reactions, we carried out exchange studies in D2O, and X‐ray crystallography studies. The former established that H–D exchange within acetaldehyde is catalyzed by 4‐OT and that the Pro1 residue is crucial for this activity. The latter showed that Pro1 of 4‐OT had reacted with acetaldehyde to give an enamine species. These results provide evidence of the mechanism of the 4‐OT‐catalyzed aldol and Michael‐type addition reactions in which acetaldehyde is activated for nucleophilic addition by Pro1‐dependent formation of an enamine intermediate.